The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00247-007-0625-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiation doses to children with shunt-treated hydrocephalus

Abstract: None of the children was exposed to doses known to cause deterministic effects. However, since the threshold for radiation-induced damage is not known with certainty, alternative modalities such as US and MRI should be used whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…4,5 Given the substantial morbidity and mortality associated with shunt malfunctions, current practice relies heavily on emergent neuroimaging, most commonly cranial CT. [6][7][8][9][10] Repeated CT scans expose children to a cumulative dose of ionizing radiation that has been associated with a significant increase in lifetime malignancy risk. [11][12][13] Thus, children with ventricular shunts are among the most vulnerable populations to the long-term deleterious effects of ionizing radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Given the substantial morbidity and mortality associated with shunt malfunctions, current practice relies heavily on emergent neuroimaging, most commonly cranial CT. [6][7][8][9][10] Repeated CT scans expose children to a cumulative dose of ionizing radiation that has been associated with a significant increase in lifetime malignancy risk. [11][12][13] Thus, children with ventricular shunts are among the most vulnerable populations to the long-term deleterious effects of ionizing radiation exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Robbins29 found that for three selected malignancies the cumulative effective dose ranged from 109 to 152 mSv. Holmedal et al 30 investigated the estimated cumulative effective dose of CT scans in children with shunted hydrocephalus, and calculated a total effective dose ranging from 2.3 to 63.8 mSv. Brunetti et al 31 investigated diagnostic radiation exposure in paediatric trauma patients ranging from 0 to 73.5 mSv (mean 12.8 mSv).…”
Section: Discussionmentioning
confidence: 99%
“…This potential risk has led to the common practice of ordering a cranial CT scan for most children with VP shunt presenting to the ED following a minor head trauma [ 109 ]. However, it must be taken into account that children with ventricular shunt are exposed to repeated CT scans for their underlying condition and additional CT scans following a head trauma contribute to the cumulative risk of repeated radiation exposures [ 110 ].…”
Section: Diagnosis Of Clinically Important Traumatic Brain Injurymentioning
confidence: 99%